Barn owls (Tyto alba) in western North America: phylogeographic structure, connectivity, and genetic diversity - Andrew C. Huang; John E. Elliott; Kimberly M. Cheng; Kermit Ritland; Carol E. Ritland; Sarah K. Thomsen; Sofi Hindmarch; Kathy Martin (Conservation Genetics, 2016)

Phylogeography and population history of Leopardus guigna, the smallest American felid - Constanza Napolitano; Warren E. Johnson; Jim Sanderson; Stephen J. O’Brien; A. Rus Hoelzel; Rachel Freer; Nigel Dunstone; Kermit Ritland; Carol E. Ritland; Elie Poulin (Conservation Genetics, 2014)

SNP discovery, gene diversity, and linkage disequilibrium in wild populations of Populus tremuloides - Colin T. Kelleher; Jennifer Wilkin; Jun Zhuang; Andrés Javier Cortés; Álvaro Luis Pérez Quintero; Thomas F. Gallagher; Jörg Bohlmann; Carl J. Douglas; Brian E. Ellis; Kermit Ritland (Tree Genetics & Genomes, 2012)

Genomics of a phylum distant from flowering plants: conifers - Kermit Ritland (Tree Genetics & Genomes, 2012)

Long‐distance gene flow and adaptation of forest trees to rapid climate change - Antoine Kremer; Ophélie Ronce; Juan J. Robledo‐Arnuncio; Frédéric Guillaume; Gil Bohrer; Ran Nathan; Jon R. Bridle; Richard Gomulkiewicz; Etienne K. Klein; Kermit Ritland; Anna Kuparinen; Sophie Gerber; et al. (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 378–392 Abstract Forest trees are the dominant species in many parts of the world and predicting how they might respond to climate change is a vital global concern. Trees are capable of long‐distance gene flow, which can promote adaptive evolution in novel environments by increasing genetic variation for fitness. It is unclear, however, if this can compensate for maladaptive effects of gene flow and for the long‐generation times of trees. We critically review data on the extent of long‐distance gene flow and summarise theory that allows us to predict evolutionary responses of trees to climate change. Estimates of long‐distance gene flow based both on direct observations and on genetic methods provide evidence that genes can move over spatial scales larger than habitat shifts predicted under climate change within one generation. Both theoretical and empirical data suggest that the positive effects of gene flow on adaptation may dominate in many instances. The balance of positive to negative consequences of gene flow may, however, differ for leading edge, core and rear sections of forest distributions. We propose future experimental and theoretical research that would better integrate dispersal biology with evolutionary quantitative genetics and improve predictions of tree responses to climate change.

Estimating selfing rates from reconstructed pedigrees using multilocus genotype data - JINLIANG WANG; YOUSRY A. EL‐KASSABY; KERMIT RITLAND (Molecular Ecology, 2012)
Several methods have been developed to estimate the selfing rate of a population from a sample of individuals genotyped for several marker loci. These methods can be based on homozygosity excess (or inbreeding), identity disequilibrium, progeny array (PA) segregation or population assignment incorporating partial selfing. Progeny array–based method is generally the best because it is not subject to some assumptions made by other methods (such as lack of misgenotyping, absence of biparental inbreeding and presence of inbreeding equilibrium), and it can reveal other facets of a mixed‐mating system such as patterns of shared paternity. However, in practice, it is often difficult to obtain PAs, especially for animal species. In this study, we propose a method to reconstruct the pedigree of a sample of individuals taken from a monoecious diploid population practicing mixed mating, using multilocus genotypic data. Selfing and outcrossing events are then detected when an individual derives from identical parents and from two distinct parents, respectively. Selfing rate is estimated by the proportion of selfed offspring in the reconstructed pedigree of a sample of individuals. The method enjoys many advantages of the PA method, but without the need of a priori family structure, although such information, if available, can be utilized to improve the inference. Furthermore, the new method accommodates genotyping errors, estimates allele frequencies jointly and is robust to the presence of biparental inbreeding and inbreeding disequilibrium. Both simulated and empirical data were analysed by the new and previous methods to compare their statistical properties and accuracies.

Multivariate analysis of digital gene expression profiles identifies a xylem signature of the vascular tissue of white spruce (Picea glauca) - Rokneddin Albouyeh; Nima Farzaneh; Jörg Bohlmann; Kermit Ritland (Tree Genetics & Genomes, 2010)

Identification of COS markers in the Pinaceae - Cherdsak Liewlaksaneeyanawin; Jun Zhuang; Michelle Tang; Nima Farzaneh; Gillian Lueng; Claire Cullis; Susan Findlay; Carol E. Ritland; Jörg Bohlmann; Kermit Ritland (Tree Genetics & Genomes, 2009)

An AFLP linkage map for Douglas-fir based upon multiple full-sib families - Nicholas K. Ukrainetz; Kermit Ritland; Shawn D. Mansfield (Tree Genetics & Genomes, 2008)

Identification of quantitative trait loci for wood quality and growth across eight full-sib coastal Douglas-fir families - Nicholas K. Ukrainetz; Kermit Ritland; Shawn D. Mansfield (Tree Genetics & Genomes, 2008)

Characterization of EST-SSRs in loblolly pine and spruce - Yanik Bérubé; Jun Zhuang; Dainis Rungis; Steven Ralph; Jörg Bohlmann; Kermit Ritland (Tree Genetics & Genomes, 2007)

Genomics of hybrid poplar ( Populus trichocarpa × deltoides ) interacting with forest tent caterpillars ( Malacosoma disstria ): normalized and full‐length cDNA libraries, expressed sequence tags, and a cDNA microarray for the study of insect‐induced defences in poplar - STEVEN RALPH; CLAIRE ODDY; DAWN COOPER; HESTHER YUEH; SHARON JANCSIK; NATALIA KOLOSOVA; RYAN N. PHILIPPE; DANA AESCHLIMAN; RICK WHITE; DEZENE HUBER; CAROL E. RITLAND; FRANÇOIS BENOIT; et al. (Molecular Ecology, 2006)
As part of a genomics strategy to characterize inducible defences against insect herbivory in poplar, we developed a comprehensive suite of functional genomics resources including cDNA libraries, expressed sequence tags (ESTs) and a cDNA microarray platform. These resources are designed to complement the existing poplar genome sequence and poplar ( Populus spp.) ESTs by focusing on herbivore‐ and elicitor‐treated tissues and incorporating normalization methods to capture rare transcripts. From a set of 15 standard, normalized or full‐length cDNA libraries, we generated 139 007 3′‐ or 5′‐end sequenced ESTs, representing more than one‐third of the c. 385 000 publicly available Populus ESTs. Clustering and assembly of 107 519 3′‐end ESTs resulted in 14 451 contigs and 20 560 singletons, altogether representing 35 011 putative unique transcripts, or potentially more than three‐quarters of the predicted c. 45 000 genes in the poplar genome. Using this EST resource, we developed a cDNA microarray containing 15 496 unique genes, which was utilized to monitor gene expression in poplar leaves in response to herbivory by forest tent caterpillars ( Malacosoma disstria ). After 24 h of feeding, 1191 genes were classified as up‐regulated, compared to only 537 down‐regulated. Functional classification of this induced gene set revealed genes with roles in plant defence (e.g. endochitinases, Kunitz protease inhibitors), octadecanoid and ethylene signalling (e.g. lipoxygenase, allene oxide synthase, 1‐aminocyclopropane‐1‐carboxylate oxidase), transport (e.g. ABC proteins, calreticulin), secondary metabolism [e.g. polyphenol oxidase, isoflavone reductase, (–)‐germacrene D synthase] and transcriptional regulation [e.g. leucine‐rich repeat transmembrane kinase, several transcription factor classes (zinc finger C3H type, AP2/EREBP, WRKY, bHLH)]. This study provides the first genome‐scale approach to characterize insect‐induced defences in a woody perennial providing a solid platform for functional investigation of plant–insect interactions in poplar.

Multilocus estimation of pairwise relatedness with dominant markers - KERMIT RITLAND (Molecular Ecology, 2005)
Estimators for pairwise relatedness designed for dominant markers are derived, based on a genetic model that accounts for the full structure of pairwise relatedness between two individuals at a diploid locus with dominance. They jointly estimate ‘relatedness’ and ‘fraternity’, in which case the estimators are inherently multilocus, as at least two loci of differing gene frequency are required. Extensions to cases of zero fraternity and isolation by distance (inbreeding) are also examined. Properties of estimators are examined by simulation and compared to the estimator of Hardy. The most statistical power for pairwise relatedness occurs when roughly half of individuals are the recessive phenotype. Estimation procedures are implemented in the computer program mark.

Robust simple sequence repeat markers for spruce (Picea spp.) from expressed sequence tags - Dainis Rungis; Yanik Brub; Jun Zhang; Steven Ralph; Carol E. Ritland; Brian E. Ellis; Carl Douglas; Jrg Bohlmann; Kermit Ritland (Theoretical and Applied Genetics, 2004)

Joining genetic linkage maps using a joint likelihood function - Xin-Sheng Hu; Carol Goodwillie; Kermit M. Ritland (Theoretical and Applied Genetics, 2004)

Single-copy, species-transferable microsatellite markers developed from loblolly pine ESTs - Cherdsak Liewlaksaneeyanawin; Carol E. Ritland; Yousry A. El-Kassaby; Kermit Ritland (Theoretical and Applied Genetics, 2004)

Marker‐inferred relatedness as a tool for detecting heritability in nature - Kermit Ritland (Molecular Ecology, 2000)
This paper presents a perspective of how inferred relatedness, based on genetic marker data such as microsatellites or amplified fragment length polymorphisms (AFLPs), can be used to demonstrate quantitative genetic variation in natural populations. Variation at two levels is considered: among pairs of individuals within populations, and among pairs of subpopulations within a population. In the former, inferred pairwise relatedness, combined with trait measures, allow estimates of heritability ‘in the wild’. In the latter, estimates of Q ST are obtained, in the absence of known heritabilities, via estimates of pairwise F ST . Estimators of relatedness based on the ‘Kronecker operator’ are given. Both methods require actual variation of relationship, a rarely studied aspect of population structure, and not necessarily present. Some conditions for appropriate population structures in the wild are identified, in part through a review of recent studies.

Impact of selection and breeding on the genetic diversity in Douglas-fir - Yousry A. El-Kassaby; Kermit Ritland (Biodiversity and Conservation, 1996)

Genetic variation in low elevation Douglas-fir of British Columbia and its relevance to gene conservation - Yousry A. El-Kassaby; Kermit Ritland (Biodiversity and Conservation, 1996)